University Student-parents’ Experiences in the UAE during COVID-19: Future Implications for Higher Education - Martina Dickson; Rehab Al Hakmani; Melissa McMinn; Jessica Midraj; Deena Elsori; Prospera Tedam (Gulf Education and Social Policy Review)
The COVID-19 pandemic began in 2020 and threw higher education institutions worldwide into a rapid transition from face-to-face to online learning modes. While students everywhere were grappling with the changes to their learning experiences, those with parenting responsibilities had additional pressures. This study investigated how university student-parents across the United Arab Emirates experienced the change, and their perceptions of the impact of COVID- 19 on their studies. One hundred seventy-five students responded to a questionnaire exploring domains such as their domestic set-up for study, levels of support from family and their institutions, and the situation’s impact on their learning, well-being, and peer and instructor interactions. It was found that while many students relished being more involved with their children’s online schoolwork, this caused tremendous strain for some. Many students had responsibility for at least one child beside them as they studied, leading to multiple distractions that affected their learning and ability to meet deadlines. While most students reported keeping up social support networks with peers, a majority also stated feeling less supported academically by peers and faculty. Many students also felt that their mental health and wellbeing had been diminished due to the situation. The implications of the findings to higher education are discussed.